Program Perawatan Komunikasi Satelit (VSAT) Di Desa Tumpak Lombok Tengah - Made Sutha Yadnya; Sultan Sultan; Agung Budi Muljono; Paniran Paniran; SMA Sasongko; I Made Ari Nrartha (Jurnal Gema Ngabdi, 2023)
Satellite communications, especially VSAT in Tumpak Village, are often disrupted, so the Electrical Engineering Department team at the University of Mataram did community service. A maintenance program was carried out to maintain the continuity of satellite communications, especially VSAT, which was carried out with moderate results because the equipment has been used for more than 5 years. The provider has changed and the available bandwidth is still small, it needs to increase the speed, but the finances are also big for the village, they have to have a reserve fund